2017
DOI: 10.5456/wpll.19.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the learning experiences of older mature undergraduate students

Abstract: Mature students have been a significant feature of UK higher education for at least 40 years. Categorising all undergraduates who started their degrees over the age of 2, as mature masks significant diversity. Older mature students have been shown to get better degree outcomes than younger mature students and young students. This study explores the learning experience of six older mature students, who started their studies over the age of 40, in order to better understand this understudied group. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Mature students have been a growing group of applicants to higher education for several decades (Evans & Nation, 1996;Pearce, 2017;Schuetze, 2014), although application numbers have fallen in recent years (UCAS, 2017). The Universities and Colleges Admissions Service (UCAS) (2017) found that in 2017, 10.4% of successful HE applicants from the UK were mature, and in 2018, the number of acceptances for students aged 26 and over increased by 6.7% (UCAS, 2018).…”
Section: Mature Studentsmentioning
confidence: 99%
“…Mature students have been a growing group of applicants to higher education for several decades (Evans & Nation, 1996;Pearce, 2017;Schuetze, 2014), although application numbers have fallen in recent years (UCAS, 2017). The Universities and Colleges Admissions Service (UCAS) (2017) found that in 2017, 10.4% of successful HE applicants from the UK were mature, and in 2018, the number of acceptances for students aged 26 and over increased by 6.7% (UCAS, 2018).…”
Section: Mature Studentsmentioning
confidence: 99%
“…Literature on NTSs, centered on late admission to HE, generically refers to them as "mature students" (Amorim, 2018;Broadhead, 2020;Pearce, 2017). The age that defines these students varies from country to country, but they are at least 21 years old (Baptista, 2013;Broadhead, 2020;Heagney & Benson, 2017).…”
Section: Non-traditional Students (Ntss)mentioning
confidence: 99%
“…These influences can sometimes trigger a powerful emotional reaction which then limits new mathematical learning (Lee et al, 2018) Strategies for teaching and learning mathematics Adult learners often have complex lives (Mason, 2018) and face particular challenges and barriers (Mark, 2018). They may, for example, struggle with time management or lack of confidence (Pearce, 2017). Their learning journeys may be 'fraught and stressful' (Pearce, 2017: 70) as they navigate their different roles as students, carers and employees.…”
Section: Barriers To Learning Mathematicsmentioning
confidence: 99%
“…These participants formed a belief, a fixed mindset (Dweck, 2006), that they could not do mathematics. This type of belief creates a barrier to motivation (Pearce, 2017).…”
Section: Barriers To Learning Mathematicsmentioning
confidence: 99%